PENGARUH KEPEMIMPINAN, KOMUNIKASI, DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA PT. PLN (Persero) APJ SEMARANG - Mamik Zulfa Setia Ningsih, 11.05.51.0045 (Students Journal of Economic and Management, 2015)
This study analyzed the effect of leadership, communication, and motivation on employee performance. Object of study in this paper is PT. PLN (Persero) APJ Semarang. The sampling technique in this research is using purposive sampling of 100 respondents in the sample data collection method using a questionnaire (questionnaire) by distributing a list of questions to the respondent in order to obtain information. The research objective was formulated to determine the effect of leadership, communication, and motivation on employee performance. The data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of the instrument, regression analysis, to examine the influence of each partially independent variables tested by regression analysis. The results of the research are: (1). Leadership has a positive and significant impact on employee performance. (2). The communication has a positive and significant impact on employee performance. (3). Motivation has a positive and significant impact on employee performance. Keywords: Leadership, communication, motivation and employee performance.